2009
DOI: 10.1038/nature08309
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in IL28B predicts hepatitis C treatment-induced viral clearance

Abstract: Chronic infection with hepatitis C virus (HCV) affects 170 million people worldwide and is the leading cause of cirrhosis in North America. Although the recommended treatment for chronic infection involves a 48-week course of peginterferon-alpha-2b (PegIFN-alpha-2b) or -alpha-2a (PegIFN-alpha-2a) combined with ribavirin (RBV), it is well known that many patients will not be cured by treatment, and that patients of European ancestry have a significantly higher probability of being cured than patients of African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

180
3,167
43
80

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 3,228 publications
(3,499 citation statements)
references
References 18 publications
180
3,167
43
80
Order By: Relevance
“…Genetic and functional studies have identified key molecules and processes involved in clearing HCV spontaneously and using interferon (IFN)‐α based therapies 3, 4, 5, 6, 7, 8, 9. These studies have implicated both innate and adaptive mechanisms in clearing HCV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and functional studies have identified key molecules and processes involved in clearing HCV spontaneously and using interferon (IFN)‐α based therapies 3, 4, 5, 6, 7, 8, 9. These studies have implicated both innate and adaptive mechanisms in clearing HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most impressive findings from Gene Wide Association Studies (GWAS) to date has been the identification of single nuclear polymorphisms (SNPs) upstream of IFN‐λ3 which are protective against HCV chronicity and treatment failure 3, 4, 5, 6, 7. This has been fine mapped to the TT/‐G polymorphism at rs67272382 in a CpG island, which is in strong linkage disequilibrium with IFN‐λ3 and is most likely to be the causal variant, with the possibility of defining a new type 3 IFN, IFN‐λ4 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The three genes encode IFN-k1 (IL29), IFN-k2 (IL28A), and IFN-k3 (IL28B). The same set of SNPs was subsequently associated with natural clearance of HCV.…”
mentioning
confidence: 99%
“…Although recent findings indicate that the interleukin-28B polymorphism explains approximately half of the treatment differences between African American and white patients, other factors, including cholesterol levels and statin use, may also play a role in virological response. 2 Recent evidence from small retrospective studies suggests that elevated low-density lipoprotein (LDL) levels may be associated with higher SVR rates in patients infected with HCV genotype 1. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In vitro data suggest that lipid-lowering agents (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors or statins) may inhibit viral replication.…”
mentioning
confidence: 99%